Technical Project Management in Living and Geometric Order - Russell, Jeffrey; Pferdehirt, Wayne; Nelson, John; Open Textbook Library (Open Textbook Library, 2018)
The Technical Project Management class is designed to help students build on their past experiences and develop effective strategies for managing complex technical projects, with an emphasis on applying project management concepts to real-world problems. In the weekly web conferences, the class comes together in community to discuss the lesson topics, considering the practical applications of the concepts in each subject area.
Chapter 1: Project Management Foundations: Principles and Concepts -- Chapter 2: Project Selection and Portfolio Management -- Chapter 3: Project Initiation, Scope, and Structure -- Chapter 4: Proposals and Contracts -- Chapter 5: Team Formation, Team Management, and Project Leadership -- Chapter 6: Project Planning -- Chapter 7: Project Scheduling -- Chapter 8: Managing Project Risks -- Chapter 9: Managing Project Value, Budgets, and Costs -- Chapter 10: Allocating and Managing Constrained Resources -- Chapter 11: Project Monitoring, Analytics, and Control -- Chapter 12: Improving Project Performance Through Project Reviews -- Chapter 13: Critical Project Management Skills: Negotiation -- Chapter 14: Personal and Organizational Project Management Growth -- Chapter 15: Putting It All Together
In English.
Description based on online resource
Keywords: Management -- Textbooks; Academic achievement -- Textbooks; Business -- Textbooks